CHRONIC PAIN SELF-EFFICACY AS A MEDIATOR OF THE LINK BETWEEN ROMANTIC ATTACHMENT INSECURITY, INDIVIDUAL FUNCTIONING, AND COUPLE SATISFACTION: A PRELIMINARY STUDYS - Martel, Marie-Eve; Lafontaine, Marie-France; Thériault, Anne; Balbinotti, Marcos (Revista Prâksis, 2016)
This preliminary study was inspired by the Attachment-Diathesis Model of Chronic Pain (ADMoCP) and examined pain self-efficacy as a mediator of the relation between people’s insecure romantic attachment and individual functioning, as well couple satisfaction. This study used a sample of 45 adults with chronic pain from the community who have been in couple relationships for at least 6 months. Participants completed self-report measures. Direct links were obtained between 1) insecure romantic attachment (anxiety over abandonment) and pain self-efficacy, 2) pain self-efficacy and individual functioning, 3) insecure romantic attachment and low individual functioning, and 4) insecure romantic attachment and lower couple satisfaction. Results also showed that pain self-efficacy significantly mediates the relation between anxiety over abandonment and individual functioning, thus adding to existing literature as well as providing more support for the ADMoCP. Future research directions are discussed along with clinical implications. Keywords: Chronic Pain. Romantic Attachment. Pain Self-Efficacy. Individual Functioning. RESUMO Este estudo preliminar foi inspirado no Attachment-Diathesis Model of Chronic Pain – ADMoCP e investigou a autoeficácia no manejo da dor como um mediador da ligação entre estilo de apego inseguro nas relações afetivas, funcionamento individual e satisfação conjugal. Este estudo utilizou uma amostra de 45 adultos da comunidade com dor crônica e que estavam em um relacionamento há pelo menos 6 meses. Participantes responderam a questionários de autorrelato. Foram obtidas relações diretas entre 1) estilo de apego inseguro nas relações afetivas (ansiedade de abandono) e autoeficácia no manejo da dor, 2) autoeficácia no manejo da dor e funcionamento individual, 3) estilo de apego inseguro nas relações afetivas e limitações no funcionamento individual e 4) estilo de apego inseguro nas relações afetivas e menor satisfação conjugal. Os resultados também mostraram que a autoeficácia no manejo da dor interfere significativamente na relação entre ansiedade de abandono e funcionamento individual, corroborando a literatura existente bem como fornecendo mais suporte para a ADMoCP. São discutidas futuras direções de pesquisa bem como implicações clínicas. Palavras-chave: Dor Crônica. Apego nas relações afetivas. Autoeficácia no manejo da dor. Funcionamento Individual.